ANALISIS SWOT PADA UMKM (CHEESE ROLL) - Septiana Cahyaningrum Tarmono Putri; Tyna Yunita, Annisa Azahra Aulia, Donni Ferdinan Irawan (CV. ADIBA AISHA AMIRA, 2023)
Entrepreneurship is a person's ability to create jobs by combining creative and innovative sides that are useful for society. Cheese Roll is a type of roll cake or bread filled with cheese. The food business is one business that is said to never “die” because everyone is always looking for it to meet their needs. In this day and age, there are many opportunities to set up businesses, both individuals and franchises, especially food businesses, which are quite easy for prospective business people who have a culinary hobby to do. This can be seen from the various types of food, from main dishes to snacks, and the prices vary from cheap to expensive. Business owners who are interested in opening a business in the form of snacks are businesses in the food sector that offer the latest innovations in the types of snacks commonly known as desserts. This effort began with the course in the Economics study program with the idea of introducing students and the public to real-world business practices. This business offers other commonly found dishes and flavors of desserts